2023
DOI: 10.26668/businessreview/2023.v8i2.1550
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Investigation of Absorptive Capacity on Technology Transfer Effectiveness Through Organizational Innovation

Abstract: Purpose:   Achieving technology transfer effectiveness (TTE) remains challenging in developing and underdeveloped economies to improve social infrastructures and develop economic systems. Bringing effectiveness in technology transfer is a complicated process for organizations that require improvement in their absorptive capacity (ACAP) and organizational innovation (OI). In the Information and communication technology (ICT) sector of Pakistan, technology transfer is ineffective due to a lack of ACAP and OI. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 98 publications
0
1
0
Order By: Relevance
“…Exploitation refers to a company's ability to develop and use procedures, Several studies have confirmed the importance of absorptive capacity in creating a competitive advantage in organizations (Soo et al, 2016). The results of several studies such as those by Tsai (2001), Eastburn, (2018, and Costa and Monteiro (2018) demonstrated that absorptive capacity plays a significant role in innovation and therefore in increasing organizational and business performanc (Hafeez et al, 2023).…”
Section: Absorptive Capacitymentioning
confidence: 99%
“…Exploitation refers to a company's ability to develop and use procedures, Several studies have confirmed the importance of absorptive capacity in creating a competitive advantage in organizations (Soo et al, 2016). The results of several studies such as those by Tsai (2001), Eastburn, (2018, and Costa and Monteiro (2018) demonstrated that absorptive capacity plays a significant role in innovation and therefore in increasing organizational and business performanc (Hafeez et al, 2023).…”
Section: Absorptive Capacitymentioning
confidence: 99%
“…Knowledge is considered a company’s primary strategic resource [ 23 ], which generates a sustainable competitive advantage [ 24 ]. Over the last few decades, due to the massive access to information, knowledge has become an essential commodity for countries’ economic growth as well as for companies’ competitive advantages at the organizational level [ 25 ]. Thus, knowledge and its management are part of the inputs required to innovate.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For this reason, companies have to have a culture of continuous learning to survive in today's world. In the literature conveys in three categories (Hafeez et al,2020).…”
Section: Learning Organizationmentioning
confidence: 99%